2017
DOI: 10.1016/j.cell.2017.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Egg Coat-Sperm Recognition at Fertilization

Abstract: SummaryRecognition between sperm and the egg surface marks the beginning of life in all sexually reproducing organisms. This fundamental biological event depends on the species-specific interaction between rapidly evolving counterpart molecules on the gametes. We report biochemical, crystallographic, and mutational studies of domain repeats 1–3 of invertebrate egg coat protein VERL and their interaction with cognate sperm protein lysin. VERL repeats fold like the functionally essential N-terminal repeat of mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 74 publications
1
91
0
Order By: Relevance
“…Although high‐resolution structural information is available on both mouse ZP2 ZP‐N1 (Raj et al, 2017) and ZP‐C (Bokhove et al, 2016; Figure 2), it is unknown how cleavage of the protein's ZP‐N2 domain mechanistically induces ZP hardening and blocks sperm‐binding. Together with ZP‐N1 and ZP‐N3 (Figure 1), ZP2 ZP‐N2 is thought to constitute protrusions that project from the ZP filament core (Monné et al, 2008; Wassarman & Mortillo, 1991).…”
Section: Cg Exocytosis Modifies the Zp After Fertilizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Although high‐resolution structural information is available on both mouse ZP2 ZP‐N1 (Raj et al, 2017) and ZP‐C (Bokhove et al, 2016; Figure 2), it is unknown how cleavage of the protein's ZP‐N2 domain mechanistically induces ZP hardening and blocks sperm‐binding. Together with ZP‐N1 and ZP‐N3 (Figure 1), ZP2 ZP‐N2 is thought to constitute protrusions that project from the ZP filament core (Monné et al, 2008; Wassarman & Mortillo, 1991).…”
Section: Cg Exocytosis Modifies the Zp After Fertilizationmentioning
confidence: 99%
“…On the basis of the appearance of multiple bands of ~20–35 kDa that reacted with antibodies raised against its ZP‐N1 domain (Burkart et al, 2012; Greenhouse, Castle, & Dean, 1999), it was suggested that post‐fertilization processing of mouse ZP2 is not limited to the LADE sequence, but also involves additional cleavages at positions 54 DE 55 and 127 DD 128 (Burkart et al, 2012). Considering the disulfide bond pattern of ZP2 ZP‐N1 (Raj et al, 2017), proteolysis at these secondary sites should release a peptide of ~8.7 kDa that would also carry an N ‐glycan attached to N83 (Boja et al, 2003); as a result, ZP2f would be expected to show a ~10‐kDa shift in SDS‐PAGE migration relative to ZP2, even when analyzed in nonreducing conditions. Consistent with the fact that such a shift was not observed experimentally (Bleil et al, 1981), it was recently shown that the heterogeneity of the N‐terminus of ZP2f is caused by variable N ‐glycosylation (Tokuhiro & Dean, 2018).…”
Section: Cg Exocytosis Modifies the Zp After Fertilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Slithering through the forest of egg coat materialsknown affectionately to the human ART community as the zona pellucida-is not simply a case of sink or swim! Rather, reports on the molecular structure of egg coat materials, including the mammalian zona pellucida component ZP2, have now revealed the presence of a sophisticated and apparently evolutionarily conserved mechanism for sperm penetration [4]. The proposed gating mechanism involves interaction of sperm lysins with ZP2 effecting creation of pores through which motile sperm can pass.…”
mentioning
confidence: 99%